Kemampuan Menulis Deskripsi Nilai Moral pada Film “Ketangen” Karya Deean Kesenian Bangka Barat Kelas XI SMAN 5 Tangerang Selatan - Pratiwi, Euis Fajriani Putri; Hindun, Hindun (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2022)
This research is about knowing the skills of writing a description of the moral values ​​of the short film "Ketangen" by the West Bangka Arts Council in class XI students of SMAN 5 South Tangerang in the 2020/2021 academic year. The subject of this research is a short film media entitled "Ketangen".  The object of this research is the students of class XI IPS 3 odd semester, totaling 41 students. The research method used is descriptive qualitative. Data analysis techniques in this study are analysis before going to the field, data reduction, data presentation from the results of data reduction, and data verification. The researcher uses the short film “Ketangen” which has been downloaded from YouTube. The results show that the moral values ​​in the short film "Ketangen" are politeness, mutual respect, mutual respect, hard work, never give up, not spoiled, not lazy and patience.  At SMAN 5, South Tangerang City, it turned out that using the film "Ketangen" as a medium in learning descriptive paragraphs could change the value of students' writing skills so that the average acquisition = 69.80.  As detailed, 6 students got very good category, 8 students were in good category, 4 students were in fairly good category, and 3 students were in poor category.   Tujuan penelitian ini untuk mengetahui bagaimana keterampilan siswa kelas XI SMAN 5 Tangerang Selatan dalam menulis teks deskripsi nilai moral film pendek “Ketangen” karya dewan kesenian Bangka Barat. Subjek penelitian ini adalah media film pendek yang berjudul “Ketangen”. Objek penelitian ini adalah siswa kelas XI IPS 3 semester ganjil yang berjumlah 41 siswa. Metode yang digunakan adalah deskriptif kualitatif. Teknik analisis data dalam penelitian ini yaitu analisis sebelum ke lapangan, reduksi data, penyajian data dari hasil reduksi data, dan verifikasi data. Peneliti menggunakan media film pendek “Ketangen” yang telah diunduh dari YouTube. Hasil penelitian menunjukkan bahwa nilai moral pada film pendek “Ketangen” yakni kesantunan, saling menghormati, saling menghargai, kerja keras, pantang menyerah, tidak manja, tidak malas dan kesabaran. Pada SMAN 5 Kota Tangerang Selatan ternyata menggunakan media film “Ketangen” pun dalam pembelajaran paragraf deskripsi dapat mengubah nilai keterampilan menulis siswa sehingga perolehan rata-ratanya = 69,80.